Preventing pressure ulcers in nursing homes using a care bundle: A feasibility study. (27th March 2019) - Lavallée, Jacqueline F.; Gray, Trish A.; Dumville, Jo; Cullum, Nicky
Abstract: Pressure ulcers can be painful and negatively affect health‐related quality of life and healthcare costs. Many people living in nursing homes are at risk of developing a pressure ulcer. Nursing home staff, tissue viability nurses and researchers have co‐designed the first theory and evidence‐informed care bundle specifically for nursing homes, which consists of three prevention practices (skin inspection, support surfaces, repositioning) and a range of behaviour change techniques to promote these practices. We conducted a mixed methods feasibility study of the use of this care bundle in one nursing home in the North of England using an uncontrolled, before‐and‐after study design. We collected quantitative data on pressure ulcer prevention behaviours of the nursing home staff and pressure ulcer incidence rates for 5 weeks prior to implementing the bundle. Data collection continued for a further 9 weeks during the bundle implementation phase. We explored adherence to the bundle and participants' experiences of using it. The Conceptual Framework for Implementation Fidelity and the Theoretical Domains Framework informed the semi‐structured interviews. Quantitative and qualitative data were analysed using descriptive statistics and deductive framework analysis respectively. We collected data for 462 resident bed days prior to implementing the bundle; five new pressure ulcers were recorded and repositioning was the only documented pressure ulcer prevention behaviour. We collected data for 1, 181 resident bed days during the intervention phase; no new pressure ulcers developed and the documented prevention behaviours included repositioning, skin inspection and checking support surfaces. Participants reported that the bundle enhanced the care they delivered and offered suggestions for future improvements. Our findings have highlighted a number of feasibility issues surrounding recruitment and retention, collecting data and implementation fidelity. A pressure ulcer prevention bundle specifically designed for nursing homes was acceptable. The feasibility work has highlighted the potential for the intervention and the areas that require development and refinement.